A gadolinium(III)-coumarin complex based MRI/Fluorescence bimodal probe for the detection of fluoride ion in aqueous medium. Issue 38 (21st September 2017) - Wang, Yue; Wang, Xueyi; Meng, Qingtao; Jia, Hongmin; Zhang, Run; Zhu, Peixun; Song, Renfeng; Feng, Huan; Zhang, Zhiqiang
Abstract: By virtue of high affinity of Gadolinium(III) with fluoride, a novel MRI/fluorescence bimodal probe was prepared by self-assembly of Gd(III) based contrast agent with the coumarin-based fluorophore (CL ). Upon addition of fluoride ion (F − ) to the aqueous solution of EDTA-Gd(III)-CL, the replacement of coordinationCL occurs, realizing switch-on both the longitudinal relaxivity ( r 1 ) and fluorescence responses, simultaneously. The fluorescence detection limit for fluoride ions was established at 0.15 μM. EDTA-Gd(III)-CL features of favorable selectivity towards F − for both relaxivity and fluorescence, reliability at physiological pH allow its potential application in biomedical diagnosis fields. Graphical abstract: A fluoride-specific MRI/fluorescence bimodal probe was reported.